2019
DOI: 10.1111/1365-2745.13179
|View full text |Cite
|
Sign up to set email alerts
|

How do soil micro‐organisms respond to N, P and NP additions? Application of the ecological framework of (co‐)limitation by multiple resources

Abstract: Nitrogen (N) and phosphorus (P) often limit biological processes in terrestrial ecosystems. Based on previous studies mainly focusing on plants, the concept of resource limitation has evolved towards a theory of (co)limitations by multiple resources. However, this ecological framework has not been applied to analyse how soil micro‐organisms and plants concurrently respond to N and/or P addition, and whether these responses are constrained by phylogenetic relatedness. Here, we applied this framework to analyse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 119 publications
(156 reference statements)
5
39
0
Order By: Relevance
“…The N and P pools are closely related, and their consumption processes control the N and P circulation within microorganisms [13,50]. The increase in the average value of TN in this study showed that exogenous N input alleviated nitrogen deficiency in the moso bamboo ecosystem, which is similar to the results of most studies [5,31,42,51].…”
Section: Discussionsupporting
confidence: 85%
“…The N and P pools are closely related, and their consumption processes control the N and P circulation within microorganisms [13,50]. The increase in the average value of TN in this study showed that exogenous N input alleviated nitrogen deficiency in the moso bamboo ecosystem, which is similar to the results of most studies [5,31,42,51].…”
Section: Discussionsupporting
confidence: 85%
“…The differences may have largely resulted from the greater stimulation of autotrophic respiration in croplands and grasslands than in forests, where there was no significant change (Zhou et al, 2014). Unlike in forestlands, N enrichment in grasslands often increases photosynthesis, which means that more NPP and energy are invested in roots to maintain soil/root water transport and nutrient absorption (Ma et al, 2019). This increases soil CO 2 emissions (Schindlbacher, Zechmeister-Boltenstern, & Jandl, 2009;Zhou, Talley, & Luo, 2009), and this process also occurs in wetlands (Wang, Cheng, et al, 2014;Wang, Liu, et al, 2014).…”
Section: Effects Of N Enrichment On Soil Co 2 Emissionsmentioning
confidence: 99%
“…The maps showed that soil bacterial and archaeal taxa in the alpine steppe (high soil pH) had closer relationships than in the alpine meadow (low soil pH). One plausible explanation for this observation is that the bacterial and archaeal communities in N-and P-limited alpine grasslands [55,56] are dominated by oligotrophic clades such as Actinobacteria, Acidobacteria, and ammonia-oxidizing archaea [38,57]. Therefore, soil bacterial and archaea have stronger connections in the alpine steppe (oligotrophic conditions and high soil pH) to resist pressure caused by an energy deficit [30].…”
Section: Discussionmentioning
confidence: 99%